Distal radius measurements and efficacy of fixed-angle locking volar plates - (:unkn) unknown (My University, 2014)
0

Aim: For surgical treatment of unstable distal radius fractures, fixed-angled locking volar plate fixation is becoming popular nowadays because of some advantages over other surgical techniques. In this article, we discuss the fitting of fixed-angle locking volar plates to the distal radius in relation to the changes in the distal radial angles. Materials and methods: First, we took conventional radiography images of 18 dried radii and later we measured the palmar subchondral angle, dorsal subchondral angle, mid-subchondral angle, and palmar cortical angle using lateral radiography. Results: According to the measurements, the volar subchondral angles (alpha) ranged from 10.2° to 28.1°, the middle subchondral angles ranged from 55.9° to 93.2°, the dorsal subchondral angles ranged from 77° to 109.6°, and the volar cortical angles ranged from 134.5° to 158.4°. Conclusion: Although fixed-angle locking volar plates are accepted as anatomical, our measurements showed that volar cortical angles and the subchondral angles are variable. Therefore, the term anatomic distal radius volar plate should be discussed.
Keywords: Cerrahi